2015
DOI: 10.1515/bog-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Population change in the regional centres and internal periphery of the regions in Russia, Ukraine and Belarus over the period of 1990-2000s

Abstract: Abstract. The paper looks into the dynamics of the population size of Russia, Ukraine and Belarus after the census of 1989. Regions and cities of these countries were the focus of the research (territorial units level NUTS-3). The analysis addresses the question to what degree the remoteness from the regional centre, i.e. the position in the core-periphery system, influences the dynamics of the population size of the territorial units of the given level. For the analytical purposes the distinction has been mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 16 publications
1
17
0
2
Order By: Relevance
“…The demographic development of hinterland does not seem to be sustainable. The research for the previous intercensal in Russia, 1989Russia, -2002, showed that up to 40% of school graduates had been leaving regional periphery in the search of better opportunities (Karachurina and Mkrtchyan 2015;Mkrtchyan 2013). My estimates demonstrate that the depletion of Russian hinterland is becoming more and more severe.…”
Section: Estimation Of Internal Youth Migrationmentioning
confidence: 80%
See 2 more Smart Citations
“…The demographic development of hinterland does not seem to be sustainable. The research for the previous intercensal in Russia, 1989Russia, -2002, showed that up to 40% of school graduates had been leaving regional periphery in the search of better opportunities (Karachurina and Mkrtchyan 2015;Mkrtchyan 2013). My estimates demonstrate that the depletion of Russian hinterland is becoming more and more severe.…”
Section: Estimation Of Internal Youth Migrationmentioning
confidence: 80%
“…Cohort research on youth migration at sub-regional level revealed the increase in the intensity of the centripetal movement in the last intercensal period compared to the previous one (Karachurina and Mkrtchyan 2015). The pace of depopulation of the hinterland is accelerating.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…UN-Habitat reviews use population numbers (United Nations Centre for Urban Settlements, 2014). Studies of post-Soviet cities usually focus on these cities' contribution to the overall national and/or macro-regional performance (Karachurina & Mkrtchyan, 2015;Zubarevich, 2018). However, it should be noted that the leading positions regional capitals occupy within their respective territories make them to some extent comparable with the official capital (Hodos, 2011;Shagoyan, 2012;Turgel, Bozhko, & Xu, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…by almost 11%. Bignebat (2006), Mkrtchyan and Karachurina (2015), and Sardadvar and Vakulenko (2016) associate out-migration from the High North regions of Russia with labour demand insufficiency.…”
Section: Introductionmentioning
confidence: 99%